Second thoughts about privacy, safety and deception. Issue 3 (3rd July 2017) - Sorell, Tom; Draper, Heather
ABSTRACT: In this paper, we point out some difficulties with interpreting three of five principles formulated at a retreat on robot ethics sponsored by the Arts and Humanities Council and the Engineering and Physical Sciences Research Council. We also attempt to iron out some conflicts between the principles. Some of the difficulties arise from the way that the autonomy of robot users – their capacity to live by their own choices – can be a goal in the design of care robots. We discuss (a) problems for Principle 2 that arise from competing legal and philosophical understandings of privacy; (b) a tension between privacy and safety (Principles 2 and 3) and (c) some scepticism about the application of Principle 4, which addresses robot design that might result in the deception of vulnerable users.